2019
DOI: 10.1111/1467-8551.12365
|View full text |Cite
|
Sign up to set email alerts
|

Shame on Who? The Effects of Corporate Irresponsibility and Social Performance on Organizational Reputation

Abstract: This study examines the relationship between corporate irresponsibility, corporate social performance and changes in organizational reputation. By combining attribution theory with expectancy violations theory, we provide the first systematic analysis of how organizational reputations are influenced by attributions of corporate irresponsibility in the context of social expectations. Drawing on a comprehensive and unique corporate irresponsibility dataset, this study reveals that firms previously believed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 85 publications
1
100
0
1
Order By: Relevance
“…Some studies report a significant decline in reputation-based FSA following CSI (Karpoff et al, 2005;Karpoff et al, 2008;Zyglidopoulos, 2001), whereas others illustrate a nuanced process of reputation erosion, dependent on the type of firm associated with CSI (Karpoff et al, 2005). Recently, Nardella et al (2020) found that, overall, CSI does not have a significantly negative impact on firm reputation, and that the social regulation process was only enacted for firms which had been known to be highly socially responsible, and thus violated stakeholder expectations. Conversely, they also found that stakeholders' limited expectations of firms can limit their desire to sanction CSI.…”
Section: Social Regulation and Csimentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies report a significant decline in reputation-based FSA following CSI (Karpoff et al, 2005;Karpoff et al, 2008;Zyglidopoulos, 2001), whereas others illustrate a nuanced process of reputation erosion, dependent on the type of firm associated with CSI (Karpoff et al, 2005). Recently, Nardella et al (2020) found that, overall, CSI does not have a significantly negative impact on firm reputation, and that the social regulation process was only enacted for firms which had been known to be highly socially responsible, and thus violated stakeholder expectations. Conversely, they also found that stakeholders' limited expectations of firms can limit their desire to sanction CSI.…”
Section: Social Regulation and Csimentioning
confidence: 99%
“…In parallel, a social regulation perspective has also emerged; whereby MNEs are understood to be deterred from behaving irresponsibly because, in addition to the risks associated with government enforced business regulation, MNEs experience significant 'informal' pressures from a range of stakeholders (Aguilera et al, 2015;Nardella et al, 2020). From a social regulation perspective, CSI is penalized and deterred as a consequence of the disapproval and sanctions evoked by non-governmental stakeholders, that may ultimately lead to diffuse alterations in stakeholders' market and non-market behavior (Barnett et al, 2020;Kölbel et al, 2017;Oh, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several important contributions have been made on the effects of non-compliance and fraudulent behaviors on corporate reputation (e.g. Fiordelisi et al, 2014;Gottschalk and Solli-Sather, 2011;Nardella et al, 2019). However, studies have generally been sparse on the nature and consequences of situations where companies behave according to higher expectations than the law prescribes (Gunningham et al, 2004 is an exception).…”
Section: Theoretical Guidancementioning
confidence: 99%
“…This would reflect an underlying positioning against environmental issues and practices which is relatively enduring, being an expression of corporate morality. Symbolic actions and opportunistic signalling through unsubstantiated disclosures is difficult to sustain (Jones, 1995; Nardella et al ., 2020). Such evidence would also advance our knowledge of the relationships among the social and environmental sustainability pillars on which explicit evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%